EP.TH.915An Audit of BAUS Guidelines and Complications of Suprapubic Catheter Insertion. (28th October 2021) - Malik, Salim; Dermanis, Alexander; Kalejaiye, Odunayo; Dowson, Christopher
Abstract: Introduction: The National Patient Safety Agency (NPSA) noted between September 2005 to June 2009, 259 incidents relating to suprapubic catheter (SPC) insertion were reported. 9 of these were bowel perforations. BAUS produced guidelines for SPC insertion which included recommending open or ultrasound guided insertion of SPCs in patients with previous lower abdominal surgery. The aim of this audit was to assess compliance with BAUS guidelines and complications following SPC insertion. Methods: All patients who had a SPC inserted in theatre at this District General Hospital (DGH) between October 2012 to October 2019 were identified. Patient demographics, ASA grade, co-morbidities, previous abdominal surgery and complications were recorded. Results: A total of 154 patients (59.1% male; 40.3% female) were identified. Mean age was 65 and mode ASA was 3. 21 (13.6%) of patients had previous lower abdominal surgery. Of these 2 (10%) had ultrasound guided insertion, 3 (14%) were open, 11 (52%) had cystoscopy guided insertion alone and for 5 (24%) the method was unknown. 4 (2.6%) of patients had a bowel injury following SPC insertion. Discussion: At this DGH there was poor compliance with BAUS guidelines with a significant number of patients with lower abdominal surgery not having open or ultrasound guided insertion of SPC. 2.6% of patients had a bowel injury, however none of these had previous lower abdominal surgery. For these patients BAUS guidelines were adhered to, but bowel injury was not prevented. We therefore recommend the consideration of image guided insertion of SPCs in all patients where possible.